2008
DOI: 10.1021/cm7033883
|View full text |Cite
|
Sign up to set email alerts
|

Novel Route To Synthesize Complex Metal Sulfides: Hydrothermal Coupled Dissolution−Reprecipitation Replacement Reactions

Abstract: A novel route for the synthesis of complex metal sulfides using hydrothermal coupled dissolutionreprecipitation reactions is reported. Two thiospinels, (Ni,Fe) 3 S 4 (violarite) and Co 3 S 4 (linnaeite), were synthesized using (Fe,Ni) 9 S 8 (pentlandite) and Co 9 S 8 (cobaltpentlandite) as precursors. The Fe/Ni ratio of (Ni,Fe) 3 S 4 can be adjusted by varying the reaction conditions, for example, temperature (125-145 °C), pH (2.90, 3.90, 5.00), and precursor stoichiometry ((Fe x Ni 1-x ) 9 S 8 , x ) 0.4, 0.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 45 publications
(61 reference statements)
2
52
0
Order By: Relevance
“…As is given from Table 1, the NiS phases have higher thermal expansion coefficient so upon rapid cooling it contracts more than the glass leaving a small space between the inclusion and the glass. NiS occurs naturally in the form of the mineral Millerite which is the β-form of NiS [32,57]. The α and β phase have different crystal structures, NiS-α has a distorted hexagonal close packed structure with the cations occupying the octahedral positions (NiAs crystal structure) [58] and the NiS-β has a rhombohedral structure [59].…”
Section: Properties Of Nickel Sulfidementioning
confidence: 99%
“…As is given from Table 1, the NiS phases have higher thermal expansion coefficient so upon rapid cooling it contracts more than the glass leaving a small space between the inclusion and the glass. NiS occurs naturally in the form of the mineral Millerite which is the β-form of NiS [32,57]. The α and β phase have different crystal structures, NiS-α has a distorted hexagonal close packed structure with the cations occupying the octahedral positions (NiAs crystal structure) [58] and the NiS-β has a rhombohedral structure [59].…”
Section: Properties Of Nickel Sulfidementioning
confidence: 99%
“…[16,17] Exploring the potential of ICDR reactions to explain the common occurrence of violarite as an alteration product of pentlandite in nature, we were able to prepare pure samples of the thiospinels (Ni,Fe) 3 S 4 (violarite) and Co 3 S 4 (linnaeite) from (Fe,Ni) 9 S 8 (pentlandite) and Co 9 S 8 (cobaltpentlandite) precursors. [17,18] In this case pentlandite and violarite both have structures based on cubic closed packed arrays of S atoms, but differ by the distributions of metals over the available interstitial octahedral and tetrahedral sites (Fig. 2).…”
Section: Synthesis Of Thiospinelsmentioning
confidence: 99%
“…Xia et al [9,18,19] found that the Fe/Ni ratio of (Ni,Fe) 3 S 4 could be adjusted by varying the reaction conditions, including temperature (125-145 ºC), pH (1 to 6), and precursor stoichiometry. Between pH 1 and 6 the reaction proceeds via an ICDR reaction, with a very sharp reaction front and porous (Ni,Fe) 3 S 4 product, as the dissolution of the pentlandite precursor is rate-limiting (Fig.…”
Section: Synthesis Of Thiospinelsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 This simplifies the data interpretation because hydrothermal reactions are usually complex and a significant change of fluid composition during the course of the reaction can change the mechanism drastically. 3,16,17 To achieve a higher working temperature and pressure, and a larger fluid volume, we have previously constructed a thermosyphon driven flow-through cell and commissioned on Wombat, Australian's new high intensity powder diffractometer at the OPAL research reactor, run by Nuclear Science and Technology Organization ͑ANSTO͒. 18 The cell worked smoothly but the thermosyphon is sensitive to local temperature and air flow variations in the neutron guide hall.…”
Section: Introductionmentioning
confidence: 99%